ANALISIS GAYA BELAJAR MAHASISWA GEN Z - Elly Aulia Sujani; Tiara Meidiani Putri; Amelia Rahayu; Wanda Hamidah; Iis Lisnawati (Jurnal Genta Mulia, 2025)
Generation Z students grew up surrounded by rapidly advancing technology and constant access to information, which shaped their unique ways of learning. This study aimed to identify the dominant learning styles among Generation Z university students to help educators tailor more effective teaching strategies. A quantitative descriptive method was applied, using a closed-ended questionnaire distributed to students from various majors. The findings reveal that visual learning is the most preferred style among respondents, followed by kinesthetic and auditory styles. Students with a visual learning style tend to absorb information more effectively through images, diagrams, and visual aids. Kinesthetic learners show a preference for hands-on activities and learning through physical involvement. Meanwhile, the auditory style ranks lowest, suggesting that lecture-based methods may not fully engage most Generation Z learners.